The Effect of Implementing Suggestopedia on English Speaking Skills of Forth Graders and their Attitudes toward it at Mayar International Schools - Carol Nairan Majali; Sadia Muhammad Salem; Nayel Darwish Al Sharaa (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The purpose of this study is to investigate the impact of implementing Suggestopedia method on English speaking skills of fourth graders and to explore their attitudes towards using it in teaching and learning at Mayar International Schools, Jordan. Participants of the study consisted of 40 students, who were grouped into a control group of (20) students and an experimental group of (20) students. Three research instruments were used to collect the data: a speaking test, a speaking checklist and an attitude questionnaire. The results of the study showed that there were statistically significant differences at (=0.05) between the mean scores of the experimental group who was were taught by Suggestopedia method and those of the control group who were taught by a conventional method on their achievement in a post-achievement speaking test, in favor of the experimental group. Moreover, the results of the study revealed that there were positive attitudes towards the implementation of Suggestopedia method in teaching and learning English speaking. Based on the results, the researchers recommend that teachers, educators, curricula planners and designers should incorporate the Suggestopedia method in teaching and learning speaking skills to fourth graders in Jordan.